The Influence of Academic Rigor on Factors Related to College Student Persistence. Issue 181 (9th March 2018) - Braxton, John M.; Francis, Clay H.
Abstract: This chapter describes research findings that show a positive relationship between higher order examination questions and core concepts of empirically supported theories of college student persistence for both residential and commuter colleges and universities.